2011
DOI: 10.1038/nmat3143
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically highly active top gold atom on palladium nanocluster

Abstract: Catalysis using gold is emerging as an important field of research in connection with 'green' chemistry. Several hypotheses have been presented to explain the markedly high activities of Au catalysts. So far, the origin of the catalytic activities of supported Au catalysts can be assigned to the perimeter interfaces between Au nanoclusters and the support. However, the genesis of the catalytic activities of colloidal Au-based bimetallic nanoclusters is unclear. Moreover, it is still a challenge to synthesize A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
469
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 580 publications
(489 citation statements)
references
References 29 publications
18
469
1
1
Order By: Relevance
“…Thus, our calculations clearly manifest that Au atoms preferentially remain on the surface by the segregation process; this will mend the defective sites on the Pt monolayers and, thus, markedly inhibit the Pd and Pt dissolution. Recent observations that preferential replacement of Au atoms takes place at the vertex or corner sites on Pd nanoparticle surfaces (1.8 nm diameter) 19 may also support our results. Accordingly, the stability of Pt ML /Pd 9 Au 1 /C under fuelcell conditions may be augmented through the inhibition of Pd dissolution.…”
Section: Structure Of Pt ML /Pdau/c Electrocatalystsupporting
confidence: 90%
“…Thus, our calculations clearly manifest that Au atoms preferentially remain on the surface by the segregation process; this will mend the defective sites on the Pt monolayers and, thus, markedly inhibit the Pd and Pt dissolution. Recent observations that preferential replacement of Au atoms takes place at the vertex or corner sites on Pd nanoparticle surfaces (1.8 nm diameter) 19 may also support our results. Accordingly, the stability of Pt ML /Pd 9 Au 1 /C under fuelcell conditions may be augmented through the inhibition of Pd dissolution.…”
Section: Structure Of Pt ML /Pdau/c Electrocatalystsupporting
confidence: 90%
“…The 3D atomic arrangement on the surface and in the core of a nanocrystal influences the electronic structure, which affects how the nanocrystal functions in catalysis or how it interacts with other components at the atomic scale (1). Introduction of atomic dopants, surface adatoms, defects, and grain boundaries alters the chemical properties of nanocrystals (2). Ensembles of synthesized nanocrystals in solution are structurally inhomogeneous due to the stochastic nature of nanocrystal nucleation and growth (3,4).…”
Section: Main Textmentioning
confidence: 99%
“…[10][11][12][13][14] Apart from the strong size dependence of the catalytic activity of gold clusters one of the most important factors in gold nanocatalysis is the support effect. 15,16 It was demonstrated that the so-called active metal oxide supports (such as, MgO, TiO 2 , Al 2 O 3 , Fe 2 O 3 , etc.)…”
Section: Introductionmentioning
confidence: 99%